METHOD OF THE UAV SAFETY VICINITY DETERMINATION - Даник, Ю. Г.; Балицький, І. І. (Science-based technologies, 2019)
The widespread use of these means, taking into account the prospects for increasing the intensity of flights of small aircraft, aggravates the problem of the safety of the flight within the border area at relatively low altitudes. In this case, it is necessary to study the possibilities of UAV deviation from collision with dynamic obstacles taking into account many factors. A large range of modern research studies is devoted to the use of UAV flight safety, but most of them focus on diverting from static hazards due to the complexity of the terrain and the presence of certain static objects (buildings, various towers, and other possible obstacles). The paper considers the option of solving the problem to ensure the safety of a flight of an unmanned aerial vehicle (UAV) in conditions of possible occurrence of dynamic obstacles. To solve this problem, a method of the UAV safety vicinity determination during its flight in order to perform heterogeneous tasks has been developed. The proposed methodology allows finding the limits of the danger area of the UAV collision with dynamic obstacles. Within the limits of this method, the following has been proposed: alternative approach to forecast movement of a dynamic obstacle, simulation of changes in UAV flight trajectory, taking into account time intervals that collectively determine the time upon obstacles detection prior to the beginning of manoeuvring, a criterion for assessing the collision hazard, which, in particular, takes into account forecasting errors. Using the developed method on the basis of the established safety vicinity it is possible: to formulate the justified requirements for the UAV manoeuvring characteristics in the process of the formation of the UAV fleet for the units of the structures of the sector of national security and defence of the state (law enforcement agencies, the Armed Forces, etc.); to determine the requirements for the on-board information system and sensors identifying dynamic obstacles. Also, the results of the study will allow an assessment of existing UAV samples from the point of view of providing safety by them under conditions of possible emergence of dynamic obstacles.